Expression of glutamine synthetase and cell proliferation in human idiopathic epiretinal membrane. Issue 1 (16th December 2005) - Kase, S; Saito, W; Yokoi, M; Yoshida, K; Furudate, N; Muramatsu, M; Saito, A; Kase, M; Ohno, S
Abstract : Background/aim: The mechanisms of the cellular origin and cell proliferation in the idiopathic epiretinal membrane (ERM) are unsolved. The aim of this study was to examine the expression of cell cycle related molecules and glutamine synthetase (GS), which is expressed in Müller cells and their processes, in ERM tissues. Methods: The ERMs were surgically removed using pars plana vitrectomy. Formalin fixed, paraffin embedded ERM tissues were analysed by immunohistochemistry with anti-cyclin D1, p27 (KIP1), proliferating cell nuclear antigen (PCNA), and GS antibodies. Results: The histopathological findings showed that all the ERMs consisted of oval or spindle mononuclear cells with thin collagen-like tissues. Immunoreactivity for GS was detected in collagen-like tissues of ERM, presenting a continuous, isodense pattern. GS immunopositive cells in all cases expressed PCNA in their nuclei. Nuclear immunoreactivity for cyclin D1 was noted in the ERM constituent cells, whereas p27 (KIP1) positive nuclei were not detected. Conclusion: Cyclin D1 and PCNA were expressed in the idiopathic ERM, which was mainly derived from Müller cells and extensions of their processes.